Fungal Keratitis Caused by Colletotrichum dematium: Case Study and Review - Buchta, Vladimír; Nekolová, Jana; Jirásková, Naďa; Bolehovská, Radka; Wipler, Jan; Hubka, Vit (Mycopathologia, 2019)
Colletotrichum species are known as important pathogens of plants with an impact on crop production. Some of these species are also known as a cause of rare ophthalmic infections in humans. A case of keratitis caused by Colletotrichum dematium after corneal trauma in a 56-year-old woman is presented. Infection was diagnosed based on positive microscopy and culture. The fungal isolate was identified by morphological characteristics and DNA sequencing of the ITS rDNA region, β-tubulin (tub2) and glyceraldehyde-3-phosphate dehydrogenase (gapdh) genes. The patient responded well to topical therapy with amphotericin B combined with intravenous amphotericin B but improvement was associated with the corneal collagen cross-linking. The review of the literature revealed another 13 cases of C. dematium keratitis, all but one patient having at least one keratitis risk factor in their history. Almost all patients (n = 12) were treated with topical polyene antibiotics (natamycin or amphotericin B), improvement and cure were achieved in eight of them.
Keywords: výsledek terapie; Young Adult; Colletotrichum; Antifungal Agents; Male; aplikace lokální; Mycoses; mladý dospělý; Adolescent; Sequence Analysis, DNA; Coelomycetous fungi; sekvenční analýza DNA; antifungální látky; Adult; Keratitis; Molecular Diagnostic Techniques; dospělí; mykózy; mužské pohlaví; Keratomycosis; mezerníky ribozomální DNA; mladiství; diagnostické techniky molekulární; keratitida; Eye Injuries; Treatment Outcome; lidé; Colletotrichum dematium; ženské pohlaví; amfotericin B; glyceraldehyd-3-fosfátdehydrogenasa (fosforylační); Therapy; Amphotericin B; Humans; mikrobiologické techniky; Administration, Topical; poranění oka; Molecular identification; DNA, Ribosomal Spacer; tubulin; Microbiological Techniques; Female; Glyceraldehyde-3-Phosphate Dehydrogenase (Phosphorylating); lidé středního věku; Glomerella; Corneal collagen cross-linking; Tubulin; Middle Aged